Solar quiet (Sq) and conductivity-depth structure of Asia sub-region using solar quiet field variation. (January 2019) - Abbas, M; Jusoh, M H; Abidin, Z Z
Abstract: The study used some selected magnetic field records to establish the equivalent external and internal ionospheric current system for the moderate solar quiet year 2012. The month-by-month behaviour of the equivalent current for both external and internal current appears stronger in local summer months (May-August) and weaker in local winter months (November-February). The current vortex appears earlier in local summer than in local winter months and disappeared in December. In each of the month, the latitudinal position of the internal Sq current vortex appeared at a considerable higher latitude than the external. A regression line fitted to the estimated conductivity values gives a profile that starts at 0.02 S/m at a depth of about 30 km and rose gradually to about 0.03 S/m seen at ∼120 km depth. Consequently the conductivity profile increases significantly to about 0.07 S/m at depth of about 400 km followed by a sharp steep increase through the transition zone and reached its peak value ∼0.3 S/m at depth of about 770 km. An evidence of discontinuity was observed at depth of about 370-440 km and 603-671 km. The sharp steep increase in conductivity profile at depth of about 400 km may be due to phase change of the mantle minerals from olivine to spinel structure.